Perbandingan Pola Bentuk Sidik Bibir Antara Suku Asli Mentawai dan Suku Campuran Mentawai - Valerio Alfa Agung Wafisal Sakoikoi; Nur In Lipoeto; Murniwati Murniwati (Faculty of Dentistry Universitas Andalas, 2019)
One of studies that plays a role in human identification in disaster and crime is forensic odontology. There are several methods of identification in forensic odontology, one of the alternative methods is cheiloscopy which is used to identify lip print pattern. Lip print pattern is identical in each person, lip print can identify gender and human race. Mentawai ethnic is a part of Proto-Melayu race which dominates Mentawai island district area. Familial relationship in Mentawai ethnic is patrilineal the tribe is derived from father’s tribe. This study aimed to compare the shape of lip print pattern between Mentawai original ethnic and Mentawai mixed ethnic. This study is a descriptive study with cross-sectional approach. The samples in this study were 16 pairs of Mentawai ethnic and 16 pairs of mixed Mentawai ethnic, the sample were selected using purposive sampling method. Lip print in study models were marked using colour pen, and the shape pattern of lip prints were observed and measured according to Suzuki and Tsuchihashi classification. Results of this study showed that there are differences in the pattern of lip prints between Mentawai ethnic and mixed Mentawai ethnic. Mentawai ethnic has dominan type of lip prints is type I, type II, and type IV while mixed Mentawai ethnic has dominan type of lip prints is type IV, type I, dan type III. The conclusion is there is a difference pattern of lip prints due to racial factors.